The lived experience of public high school students in emergency distance education - Tiro, Dexter Cuabo
Distance education (DE) is a well-studied field but situated in a pandemic. experience of this modality has led to a novel phenomenon. Emergency Distance Education (EDE) presents characteristics distinct from conventional understanding of distance learning. There is also a lack of research on DE in secondary basic education, making it important to understand what it is like to learn in EDE during a pandemic. Eight public high school students selected through typical purposeful sampling described their lived experiences in the first full year of EDE implementation. Using Descriptive Phenomenological Psychological Method of Arnedeo Giorgi (2009), a description of the general structure of thc expericnce was drawn. summarized into thematic categories that (1) clarify studcnts’ phcnomcnal context, and (2) enumerate factors enabling students to navigate through their lifcwotld toward the realization of their educational goals. Overall, their context was characterized by (a) a sense of ambivalence, i.e.. a perception of convenience amidst difficulties, a concept of self-sufficiency within feelings of isolation, provisional conformity despite doubts; and (b) a persistent negotiation of expectations with the realities of the learning environment underscored by constraint in their physical interactions, entanglement of spatial boundaries, and doubts about their learning experiences. Such context triggered a conflicted view on the teacher's presence, availability, and accessibility. The indispensability of socio-academic interactions and their interdependence as a learning community has been accentuated and compelled learners to adopt behavioral and cognitive coping strategies. The findings offer key insights to inform educators in designing educational goals and environment for distance learners.